2017
DOI: 10.1057/s41262-017-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Helping those who help us: co-branded and co-created Twitter promotion in CSR partnerships

Abstract: Partnerships between brands and non-profit-organisations (NPOs) must be strategically managed for each to maximise their benefit from the relationship. Twitter, with its potential for pass-along of messages, provides an ideal channel for reciprocal promotion within the network of an NPO and its supporting brands. For any one brand within that network, brand building will be amplified if messages are passed on to others using co-branded and/or cocreated communications, providing an opportunity for a brand to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…The second SI article unpacks co-branded and co-created Twitter promotion in CSR partnerships (Burton et al 2017). Focusing on a non-profit organisation and its networks of corporate partners, the findings reinforce earlier research that such organisations are not using Twitter to full capacity as a stakeholder engagement vehicle, leading to calls for further research to understand why.…”
Section: Special Issue: Harnessing the Power Of Brand And Co-created supporting
confidence: 58%
“…The second SI article unpacks co-branded and co-created Twitter promotion in CSR partnerships (Burton et al 2017). Focusing on a non-profit organisation and its networks of corporate partners, the findings reinforce earlier research that such organisations are not using Twitter to full capacity as a stakeholder engagement vehicle, leading to calls for further research to understand why.…”
Section: Special Issue: Harnessing the Power Of Brand And Co-created supporting
confidence: 58%
“…Previous studies suggested that organizations use social media platforms strategically to communicate their efforts with the public [47]. Our study indicates that Twitter is an important medium for organizations to communicate with stakeholders [15,60], especially for promoting, hiring, reporting, and announcing. In this regard, CSR communication in Twitter appears to be different from that of traditional mediums, being less formal and more emotional.…”
Section: Discussionmentioning
confidence: 71%
“…That is, these brands may not make full use of digital CSR communication on Twitter to actively engage customers in supporting the brands' co-creation activities. While some may argue that higher levels of follower engagement in Twitter may not be always desirable, we believe that such engagement is a crucial prerequisite for the brands to use followers to increase the reach of cocreated tweets and promote their CSR efforts and/or those of other partners in the CSR network using their own, co-created, or customer-generated tweets (Burton et al, 2017;Gensler et al, 2013;Hudson et al, 2016;Shmargad & Watts, 2016;Soboleva et al, 2017).…”
Section: Discussionmentioning
confidence: 92%